Mathxyz - upsc.xyz
0 votes
Consider the differential equation $xyp^2 - (x^2+y^2-1)p+xy = 0$ where $p = \frac{dy}{dx}$. Substituting $u=x^2$ and $v=y^2$ reduce the equation to Clairaut's form in terms of $u$, $v$ and $p'=\frac{dv}{du}$. Hence, or otherwise solve the equation.
asked Nov 12, 2017 by randomisation (1,920 points)  

1 Answer

0 votes
Best answer
$u = x^2 \implies du = 2x dx$

$v = y^2 \implies dv = 2y dy$

$p' = \frac{dv}{du} = \frac{y}{x}\frac{dy}{dx} = \frac{y}{x}p \\ \implies p = \frac{x}{y}p'$

Substituing in the given differential equation,

$xyp'^2\frac{x^2}{y^2} - (x^2+y^2-1)p'\frac{x}{y} + xy = 0 \\ \implies x^2p'^2-(x^2+y^2-1)p' + y^2 = 0 \\ \implies up'^2 - (u+v-1)p'+v=0 \\ \implies (p'-1)v = up'(p'-1)-p' \\ \implies v = up' - \frac{p'}{p'-1}$

To solve the given differential equation, just replace $p'$ by $c$ in the Clairaut's equation

$\implies v = uc-\frac{c}{c-1} \implies y^2 = cx^2 - \frac{c}{c-1}$
answered Nov 12, 2017 by randomisation (1,920 points)  
Welcome to MathXyz, where you can ask questions and receive answers from other members of the community. Please strictly ask questions from UPSC Mathematics syllabus.
36 questions
26 answers
2 comments
9 users